Islamic Business Ethics Implementation Towards Sustainibility Of The Hajj And Umrah Business Travel Agency Of Makassar City - Nurbayani Nurbayani; Muliana Muliana (LAA MAISYIR: Jurnal Ekonomi Islam, 2021)
Islamic business ethics implementation could  control  every  business activity.  This research was conducted to  analyze and  confirm  how  the  Islamic business ethics implementation in realizing  Hajj loyalty and  business sustainibilty of Hajj and  Umrah travel  agencies  in    Makassar city.  This  research was a  direct  research using  a quantitative approach, and used Structural Equation  Modeling (SEM) as analysis tool which  is PLS (Partial  Least Square) in analyzing  the  effect of the  Islamic business ethics implementation toward  business sustainibility. The  results of  the  research found  that  travel  agency managers  had  implemented  Islamic business  ethics  in operating   its   operational   activities   including    the    oneness,   the    justice,   the responsibility and  the  truth  principle  which were  quite  high so it was able  to realize business  sustainibility  or  the  existence  of  a  travel  agency  for  Hajj  and   Umrah Makassar city, especially those whom  became sample in this study. The results of this research were very encouraging information for the Hajj and Umrah in Makassar city.